Face Masks During the COVID-19 Pandemic: A Simple Protection Tool With Many Meanings - Martinelli, Lucia; Kopilaš, Vanja; Vidmar, Matjaž; Heavin, Ciara; Machado, Helena; Todorović, Zoran; Buzas, Norbert; Pot, Mirjam; Prainsack, Barbara; Gajović, Srećko (Frontiers in Public Health, 2021)
Wearing face masks is recommended as part of personal protective equipment (PPE) and as a public health measure to prevent the spread of COVID-19 pandemic. Their use, however, is deeply connected to social and cultural practices, and has acquired a variety of personal and social meanings. This article aims to identify the diversity of socio-cultural, ethical, and political meanings attributed to face masks, how they might impact public health policies, and how they should be considered in health communication. In May 2020, we involved 29 experts of an interdisciplinary research network on health and society to provide their testimonies on the use of face masks in 20 European and 2 Asian countries (China and South Korea). They reflected on regulations in the corresponding jurisdictions as well as the personal and social aspects of face mask wearing. We analyzed those testimonies thematically, employing the method of qualitative descriptive analysis. The analysis framed the four dimensions of the societal and personal practices of wearing (or not wearing) face masks: individual perceptions of infection risk; personal interpretations of responsibility and solidarity; cultural traditions and religious imprinting; and the need of expressing self-identity. Our study points to the importance for an in-depth understanding of the cultural and socio-political considerations around the personal and social meaning of mask wearing in different contexts as a necessary prerequisite for the assessment of the effectiveness of face masks as a public health measure. Improving the personal and collective understanding of citizens’ behaviors and attitudes appears essential for designing more effective health communications about COVID-19 pandemic or other global crises in the future.